Investigation of culture conditions for recombinant xylanase a production and its enzymatic hydrolysis of agricultural wastes - Tuyen, Do Thi; Thanh Tung, Vu; Nhat Linh, Nguyen; Thanh Hoang, Le; Le Thanh, Nguyen Sy; Anh Tuyet, Nguyen Thi; Thi Thao, Nguyen; Hien Trang, Nguyen Thi; Thi Trung, Nguyen; Minh Duc, Luu; Mai Anh, Dao Thi (Vietnam Journal of Biotechnology, 2023)
Xylanase A of Aspergillus niger dsm 1957 was successfully expressed in strain Pichia pastoris GS115/pXlnA in YP medium induced by methanol. Molecular weight of the recombinant xylanase A was 35 kDa, that was consistent with the theoretical calculation and the enzyme activity in the culture was 7310 U/mL. Maximal xylanase activity (11180 U/mL) was gained after culturing the recombinant yeast for 120 hours in the present of 1% methanol. Among of seven media (BMMY, MMY, MM, YPM, YPTM, YPTCM, and YP) utilized for the yeast culture, the highest activity of the produced recombinant xylanase A (21620 U/mL) was reached in BMMY medium, while the lowest activity (1410 U/mL) was found in YPTCM medium. At the appropriate conditions, the recombinant xylanase A activity was 2.96 folds higher than that expressed in normal conditions. The conditions for recombinant xylanase A enzymatic hydrolysis of several agricultural wastes were also investigated. The results showed that in appropriate conditions (40oC, 24 hours, substrate concentration of 40 mg), the highest amount of reducing sugars produced from cob, rice bran and soybean meal substrates were 0.617 ± 0.002 μmol/mL, 0.663 ± 0.002 μmol/mL, and 0.814 ± 0.003 μmol/mL, respectively. Overall, with these distinctive properties, the recombinant xylanase A may initially become a potential candidate for various industrial applications.